Sistem Pendukung Keputusan Untuk Menentukan Tujuan PPL Mahasiswa Menggunakan Metode AHP - Rahmad Al Rian; Edi Ismanto; Ambiyar Ambiyar (Jurnal Pendidikan Teknologi Informatika dan Sains, 2019)
Internship or PPL is an activity carried out by the Faculty of Teachers Training and Education students to apply their scientific competencies which have been learned during lectures in the University. It is by placing students in public or private vocational secondary schools in the city of Pekanbaru. Student placement is often not in accordance with the students expertise so that they are not able to teach with the best efforts and ability which based on scientific field of study program at the destination school. This research is to build a decision support system by using Analytical Hierarchy Process (AHP) by collaborating data in vocational school study program with student academic score data to determine the objectives of internship per student.